The Switching of the Type of a ROS Signal from Mitochondria: The Role of Respiratory Substrates and Permeability Transition - Alexey G. Kruglov; Anna B. Nikiforova (MDPI AG, 2024)
Flashes of superoxide anion (O2−) in mitochondria are generated spontaneously or during the opening of the permeability transition pore (mPTP) and a sudden change in the metabolic state of a cell. Under certain conditions, O2− can leave the mitochondrial matrix and perform signaling functions beyond mitochondria. In this work, we studied the kinetics of the release of O2− and H2O2 from isolated mitochondria upon mPTP opening and the modulation of the metabolic state of mitochondria by the substrates of respiration and oxidative phosphorylation. It was found that mPTP opening leads to suppression of H2O2 emission and activation of the O2− burst. When the induction of mPTP was blocked by its antagonists (cyclosporine A, ruthenium red, EGTA), the level of substrates of respiration and oxidative phosphorylation and the selective inhibitors of complexes I and V determined the type of reactive oxygen species (ROS) emitted by mitochondria. It was concluded that upon complete and partial reduction and complete oxidation of redox centers of the respiratory chain, mitochondria emit H2O2, O2−, and nothing, respectively. The results indicate that the mPTP- and substrate-dependent switching of the type of ROS leaving mitochondria may be the basis for O2−- and H2O2-selective redox signaling in a cell.